Expression of an abscisic acid-binding single-chain antibody influences the subcellular distribution of abscisic acid and leads to developmental changes in transgenic potato plants - Sonnewald, Uwe; et al. (Planta, 2001)
Potato (Solanum tuberosum L. cv. Desiree) plants were transformed to express a single-chain variable-fragment antibody against abscisic acid (ABA), and present in the endoplasmic reticulum at to up to 0.24% of the soluble leaf protein. The resulting transgenic plants were only able to grow normally at 95% humidity and moderate light. Four-week-old plants accumulated ABA to high extent, were retarded in growth and their leaves were smaller than those of control plants. Leaf stomatal conductivity was increased due to larger stomates. The subcellular concentrations of ABA in the chloroplast, cytoplasm and vacuole, and the apoplastic space of leaves were determined. In the 4-week-old transgenic plants the concentration of ABA not bound to the antibody was identical to that of control plants and the stomates were able to close in response to lower humidity of the atmosphere. A detailed analysis of age-dependent changes in plant metabolism showed that leaves of young transformed plants developed in ABA deficiency and leaves of older plants in ABA excess. Phenotypic changes developed in ABA deficiency partly disappeared in older plants.
Keywords: abscisic acid; single-chain antibody; Solanum (abscisic acid); transgenic potato